Kualitas Akuntansi dan Efisiensi Investasi: Peran Eksekutif Perempuan di Sektor Properti dan Real Estate - Enok Rusmanah; Tumpal Manik; Syarifuddin (urn:nbn:id:umrah-jafi.v9i1.2025.001jiafi.v9i1, 2025)
This study examines the impact of accounting quality on investment efficiency and investigates the moderating role of female executives in Indonesia’s property and real estate sector. Using data from 65 property and real estate companies listed on the Indonesia Stock Exchange (2021–2023), the study employs data panel regression analysis. The results reveal that accounting quality significantly improves investment efficiency by reducing information asymmetry and minimizing inefficient capital allocation. However, the moderating role of female executives is not significant, suggesting that their current representation in managerial positions remains limited to influencing investment outcomes. The findings emphasize the importance of transparent accounting information in enhancing investment efficiency and the potential of gender diversity to strengthen governance in capital-intensive industries